Effects of foreign direct investment in developing countries - Dietrich Kebschull (Intereconomics, 1980)
The effects of direct investments and multinational corporations remain a highly contentious issue. The author traces here the reasons for the large number of diverging statements and comments on this issue and considers what political conclusions should be drawn from this wide variety of views.
Keywords: 330; Private Investment